The Relationship between the Effectiveness of Work Health and Safety Management and Motivation Achievement with Employee Productivity (Case Study on employee PT. PLN (Persero) Transmission Implementing Unit Bogor) - Herlina, Erna; Sunaryo, Widodo; Entang, H. M (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to find efforts that can improve employee productivity through assessment of the strength relationship with the effectiveness of health and safety management and achievement motivation. The study was conducted using primary data through a survey using a questionnaire. The study was conducted on 105 employees at PT PLN (Persero) Bogor Transmission Implementing Unit with sampling techniques in the form of proportional random sampling techniques. Data were analyzed by t test, F test, coefficient of determination, and correlation test. This study concluded that, first, there is a positive and medium relationship between the effectiveness of occupational health and safety management with employee productivity with ry1 = 0.513, supported by the correlation equation Y = 29.869 + 0.532X1, meaning that each increase in one unit of work health and safety management effectiveness will improve employee productivity of 0.532. Second, there is a positive and strong relationship between achievement motivation and employee productivity with ry2 = 0.762 and supported by the correlation equation Y = -1.224 + 0.956X2, meaning that each increase in one unit of achievement motivation will increase employee productivity by 0.956. Third, there is a positive and strong relationship between the effectiveness of occupational health and safety management and achievement motivation together with employee productivity use correlation coefficient show ry12 = 0.773 supported by the regretion equation Y = -6.605 + 0.154X1 + 0.859X2. The effectiveness of occupational health and safety management and achievement motivation together have contributed to employee productivity by 59.7%.